2010
DOI: 10.1111/j.1365-2788.2010.01292.x
|View full text |Cite
|
Sign up to set email alerts
|

Describing dialogue between persons with profound intellectual and multiple disabilities and direct support staff using the scale for dialogical meaning making

Abstract: Using the S-DMM to describe dialogue with persons with profound intellectual and multiple disabilities appears to be promising. The value of the S-DMM and its consensus-rating procedure are reflected upon and discussed with regard to implications for research and practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
44
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 22 publications
2
44
0
2
Order By: Relevance
“…However, some studies have reported that the staff's judgement could enable the self-determination of adults with PIMD, and many other studies have suggested that it is important for the staff to know the person well to facilitate participation (Forster & Iacono, 2008;Hostyn et al, 2010). The fact that the staff members decide on the adults' capability makes the power relationship even more uneven and reduces the opportunities for adults with PIMD to exercise selfdetermination and autonomy in their daily lives.…”
Section: Con Clus Ionmentioning
confidence: 99%
“…However, some studies have reported that the staff's judgement could enable the self-determination of adults with PIMD, and many other studies have suggested that it is important for the staff to know the person well to facilitate participation (Forster & Iacono, 2008;Hostyn et al, 2010). The fact that the staff members decide on the adults' capability makes the power relationship even more uneven and reduces the opportunities for adults with PIMD to exercise selfdetermination and autonomy in their daily lives.…”
Section: Con Clus Ionmentioning
confidence: 99%
“…Olsson ; Hostyn et al . ); rather the focus of studies has tended to be on more readily observable and judged behaviours, such as the complexity of disability support worker (DSW) speech (Purcell et al . ; Healy & Walsh ), the use of verbal or physical modalities (Seys et al .…”
mentioning
confidence: 99%
“…Such detailed levels of analyses have been conducted in a very small number of studies (e.g. Olsson 2004;Hostyn et al 2010); rather the focus of studies has tended to be on more readily observable and judged behaviours, such as the complexity of disability support worker (DSW) speech (Purcell et al 1999;Healy & Walsh 2007), the use of verbal or physical modalities (Seys et al 1998), and the opportunities for choice making, preference indication and participation (Bloomberg et al 2003;Cannella et al 2005).…”
mentioning
confidence: 99%
“…The Scale for Dialogical Meaning Making (S‐DMM) highlights the potential value of using a consensus coding approach. Hostyn et al . (2010) in their study evaluating the efficacy of the S‐DMM outline a rigorous initial observer training process similar to other observational studies not employing consensus coding (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The Scale for Dialogical Meaning Making (S-DMM) highlights the potential value of using a consensus coding approach. Hostyn et al (2010) in their study evaluating the efficacy of the S-DMM outline a rigorous initial observer training process similar to other observational studies not employing consensus coding (e.g. Janssen et al 2004;Vervloed et al 2006), which included a review of the theoretical background of the S-DMM, and practice coding videos not included in the study.…”
Section: Potential Benefits Of Consensus Codingmentioning
confidence: 99%